Nepalese Health System Response to Fight against COVID-19 Pandemic - Awasti, Sharada; Simkhada, Padam; Magar, Sudip Ale; Teijlingen, Edwin Van (Europasian Journal of Medical Sciences, 2021)
The novel coronavirus or COVID-19 is a new highly infectious virus affecting a large population across the globe. There is no specific therapeutic drug available against COVID-19, hence the most affected public health measures need to strictly be adhered to without delay. A range of issues were reported to fight against COVID-19 in the current health system of Nepal which should be addressed to strengthen the full spectrum of the health system for its effective and sustainable response. It is crucial to understand the current health system at the local, provincial level and sincerely adhere the federal government policies and plan as per the protocol for maintaining minimum infection prevention and control measures with having preventive and safety measures to both service providers and community people. To tackle those daily increasing number of COVID-19 cases, it provides an opportunity for the three tires of governments to reprioritize the health service in the national agenda for the effective prevention and response it. Although national health policy 2019 clearly articulated the need for equitable access and quality of health care services to all. Evidence shows that Nepal is in risk zone because of comparably weak health system that should be aware of all three levels of government in Nepal and strengthen and control the present threat posed the daily increasing cases of pandemic.